Drug of Choice Treatment Syphilis in Pregnancy - Devi Putri Amalia Suryani (Journal of Social Research, 2024)
To treatment patient syphilis in pregnancy. Literatur searches use medical search egines for example Pubmen, Google Scholar and medical scientific journal. Drug of choice treatment for syphilis in pregnancy is benzathine penicilin, procaine penicillin, eritromicin or azitromicyn depending on the syphilis stage. Primary,secondary, early latent (<1 year) use benzathine penicillin G 2,4 million unit IM once over procaine penicillin 1,2 million units IM once daily for 10 day, If benzathin or procain allergy/ are not available WHO STI suggest using Erythromycin 500 mg orally four times daily for 14 days, ceftriaxone 1 g IM daily (10-14 days) or Azithromycin 2 g once orally. Late syphilis (> 2 years durations) benzathine penicillin G 2.4 million units IM once weekly for 3 consecutive weeks. Latent syphilis (unknow duration) use Benzathine penicillin G as 3 doses of 2.4 million units IM each at 1week intervals. syphilis in pregnancy must be treated adequately, so as to prevent death in infants or congenital syphilis.